Assessment of Irrigation Water Quality of Some Springs in the Al-Jabal Al-Akhdar Region, Libya - Twfeik Mohammed Elbagrmi; Mohammed Abdulhadi Al-Haen; Abdulsalam Mohammed Amharb; Issa Abdulkarim Al-Haen (African Journal of Advanced Pure and Applied Sciences, 2026)
The present study aims to assess the irrigation water quality of several springs in the Al-Jabal Al-Akhdar region, northeastern Libya, in order to determine their suitability for agricultural use, given the heavy reliance on groundwater resources in the area. Ten water samples were collected from springs distributed across several locations during the autumn of 2024. A set of physicochemical analyses was conducted, including measurements of pH and electrical conductivity (EC), as well as the concentrations of major ions such as calcium (Ca²⁺), magnesium (Mg²⁺), sodium (Na⁺), and potassium (K⁺). In addition, the Sodium Adsorption Ratio (SAR) and the Soluble Sodium Percentage (SSP%) were calculated. The results showed that pH values ranged between 6.8 and 7.9, with an average of 7.2, while electrical conductivity values ranged from 574 to 1006 µS/cm, indicating relatively moderate salinity levels. The SAR values ranged between 1.08 and 1.65, whereas SSP values varied from 31.2% to 42.3%, all of which fall within the acceptable limits for irrigation water. According to the classification of the United States Salinity Laboratory (USSL), the water samples were categorized within the classes C2–S1 and C3–S1, indicating a low sodium hazard but moderate to relatively high salinity effects. These findings suggest that the studied spring waters can be used for irrigation, provided that appropriate salinity management practices are implemented, including adequate drainage and the cultivation of relatively salt-tolerant crops. Such measures would contribute to supporting the sustainable management of water resources in the Al-Jabal Al-Akhdar region.